An integrative model of TPACK development: the interplay of teachers' digital competence and principal instructional leadership in indonesian secondary schools - Lusi Susanti; Widiawati Widiawati; Merika Setiawati; Anisah Anisah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Digital transformation in education demands the integrated development of teachers' Technological Pedagogical Content Knowledge (TPACK), which is influenced by both individual and organizational factors. This study aims to examine the influence of teachers' digital competence and principals' instructional leadership on TPACK development. This study employed a quantitative correlational design involving 77 public junior high school teachers in Pariaman City, selected using the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression using SPSS and AMOS. The results showed that teachers' digital competence and principals' instructional leadership significantly predicted TPACK. Digital competence proved to be a stronger predictor (β = 0.467) than instructional leadership (β = 0.259), with both variables together contributing significantly to the variance in TPACK (p < 0.001). These findings emphasize the importance of integrating strengthening teachers' digital competence with effective instructional leadership to support meaningful and sustainable technology integration in learning.